2021
DOI: 10.1039/d1ra06568h
|View full text |Cite
|
Sign up to set email alerts
|

Designing conductive networks of hybrid carbon enables stable and long-lifespan cotton-fiber-based lithium–sulfur batteries

Abstract: A flexible, “dead weight”-free lithium–sulfur battery substrate was prepared, and batteries using these substrates showed great electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In the SAED test of selected regions, bright diffraction spots were observed, labeled as (002), ( 102), ( 112) and (104) planes, which further confirmed their crystal structure and crystal phase composition, obviously proving that NiCoSe 2 /NC micro-flower composites have high crystallization. 58 The test results of TEM and SAED are consistent with those of XRD. 59 3.2 Electrochemical performance test of three-dimensional (3D) micro-pattern NiCoSe 2 /NC composites Fig.…”
Section: Resultssupporting
confidence: 73%
“…In the SAED test of selected regions, bright diffraction spots were observed, labeled as (002), ( 102), ( 112) and (104) planes, which further confirmed their crystal structure and crystal phase composition, obviously proving that NiCoSe 2 /NC micro-flower composites have high crystallization. 58 The test results of TEM and SAED are consistent with those of XRD. 59 3.2 Electrochemical performance test of three-dimensional (3D) micro-pattern NiCoSe 2 /NC composites Fig.…”
Section: Resultssupporting
confidence: 73%
“…48 Figure 6a shows the adsorption model and the calculated E ads between the two kinds of CNTs and the discharge product Li 2 S. It is found that the E ads between Li 2 S and P-CNTs is −0.936 eV, and that between Li 2 S and CNTs is −0.413 eV, which indicates that the adsorption effect of P-CNTs to Li 2 S is higher than the other one. Meanwhile, compared to the natural feature of weak interaction between sulfur monomers and CNTs, 49 P-CNTs have more oxygen-containing functional groups and more defects based on the above investigation, which means stronger interactions with sulfur than ordinary carbon tubes, leading to better charge transfer between S and P-CNTs, which benefits the reaction from S to Li 2 S and 34,50 which makes the redox reaction more complete and thorough. The force between Li 2 S and carbon tubes likewise determines the reaction speed when charging and discharging, which also verifies why the retention rate of cycling is high for S@P-CNTs.…”
Section: Resultsmentioning
confidence: 94%
“…These results confirm that sulfur can not only be confined within the internal cavities but also be distributed uniformly on the outer surfaces of the nanotubes. One-dimensional P-CNTs can be stacked to form a three-dimensional conductive network, which is beneficial to enhancing the electron conduction, improving the utilization rate of sulfur after sulfur loading, and lessening the interfacial reactions between carbon and the SE …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, due to the particularity of wearable electronic textiles, the mechanical and electrochemical performance requirements of energy storage equipment are higher. Traditional energy storage devices such as lithium-ion batteries, 7,8 zinc-ion batteries, 9,10 lithium−sulfur batteries, 11,12 etc., have good energy storage capability. However, most of them are solid state and inconvenient to carry, and they do not have properties such as stitching and washability.…”
Section: Introductionmentioning
confidence: 99%